GAMBARAN PENGETAHUAN PERAWAT TENTANG KOMUNIKASI SBAR - Raja Fitrina Lestari; Susi Erianti (Jurnal Keperawatan Abdurrab, 2023)
SBAR communication is used by nurses as an effective framework in conveying clear information on patients' condition to the doctor, meanwhile, its implementation requires good knowledge. It consist of Situation, Background, Assessment, as well as Recommendation and is used when making a handover to the patient. Hence, this study aims to evaluate nurses' knowledge on SBAR communication at Riau University Hospital in 2020. This was a descriptive analysis conducted with a cross-sectional design on 34 respondents selected by the total sampling technique using a questionnaire as the data. collection instrument. The results showed that majority of the nurses' overall knowledge on the SBAR communication was in the sufficient category, namely less than 32 respondents or 94.1%. Based on the results, there is need to evaluate the management of nurses' knowledge on SBAR Communication. Therefore, nurses are expected to re-evaluate SBAR communication utilization in improving patient safety.